A driving strategy of shape memory alloy wires with electric resistance modeled by logistic function for power consumption reduction. (November 2021) - Guan, Jing-Han; Pei, Yong-Chen; Wu, Ji-Tuo
Graphical abstract: Highlights: Detection method and driving strategy of shape memory alloy wires are discussed. An improved phase transformation equation with the Logistic function is proposed. SMA wires electric resistance and its rate are studied in theory and experiment. Phase transformation start/end points are detected by electric resistance method. Optimized driving strategy is proposed to reduce power consumption of SMA wires. Abstract: To propose a novel driving strategy for power consumption reduction, this paper studies the electric resistance behaviors of shape memory alloy (SMA) wires, which are heated by the short-time large current. With a concern for the relationship between electric resistance and shape memory effect, an improved phase transformation equation with the Logistic function is proposed. Moreover, based upon electric resistance and its rate, a new detection method for the driving strategy of SMA wires is proposed. The proposed method is compared with the traditional deformation detection method. The results show that the method effectively resists the interference of system noise and captures the start and end points of phase transformation. To assess the deformation response of SMA wires by the proposed method, constant load tests are conducted, which are applied with the periodic excitation signals of triangular wave, sine wave, and square wave, respectively. The experimental results show the square wave is more suitable for driving the SMA wire actuator. The heating and cooling cycle experiment verifies the effectiveness of the proposed method. Compared with the method using pulse width modulation signals, the proposed method reduces power consumption obviously, and does not need external sensors or material parameters. Based on the proposed method, the power consumption can be reduced by the optimized driving strategy, which improves the lightweight and reliability of SMA actuators.